AN EMPERICAL CRITIQUE OF AMERICAN LIBERAL DEMOCRACY IN GLOBAL ERA AFTERMATH 9/11: AN AMERICAN STUDIES APPROACH - Didik Murwantono (Universitas Stikubank (UNISBANK) Semarang, 2011)
This paper is by no means a comprehensive account of liberal democracy or more accurately, American liberal democracy in global era aftermath 9/11. In fact, it is intended to be more suggestive than comprehensive in getting any deep meaning of American Studies approach though it is characterized by more American Studies framework than controversy issues in details. In short, it is a brief note on American Studies, mainly on the subject of democracy, one of the American traits and values. American Studies itself is an international studies in studying America and its people with typical canon of interdisciplinary discipline and synthesis of knowledge Key words: American Studies, interdisciplinary approach, synthesis of knowledge, international studies